North East Frontier Agency Draft Annual Operating Plan 1972-73 - Planning Commission (Planning Commission, 1971)
The Central Sheep Farm, Shergoan is being established during 1971-72. During 1972-73 expansion and development activities will be taken up. The details of the scheme can Lassen at Appendix ’F’. Attached with the Central Sheep Breeding Farm, Shergoan, it is proposed to open a Training Centre to train to local shephards in the improved practices of sheep Husbandry wool utilisation, 1972—73, 20 Shephards will be trained in the Centre.
Draft Annual Operating Plan 1972-73
Government of Meghalaya